Lactobacillus johnsonii CRL1647, isolated from Apis mellifera L. bee-gut, exhibited a beneficial effect on honeybee colonies - Audisio, Marcela Carina (2011)
Lactobacillus johnsonii CRL1647, isolated from the intestinal tract of a honeybee and selected due to its high lactic acid production, was assayed as a monoculture on bee colony performance. It was delivered to the bees on a one litre of 125 g/l sugar-cane syrup with a final concentration of 10 5 cfu/ml lactobacilli. The bees accepted the new nourishment, which was consumed within 24-48 h and was administered in two independent trials (every 14-15 days for 3 consecutive months in one case, and once a month for 13 consecutive months in the other). From late spring - early summer (2008) the photo-records and statistical analyses revealed significant differences in the open and the operculated brood areas in the treated group compared with the control. This stimulation was observed after the first administration of the lactobacilli and maintained throughout. Also, a higher number of bees were measured in the treated group (54%) and the control (18%) with respect to the initial bees' number. Furthermore, honey storage was higher, 40% and 19%, for the treated and control groups, respectively. From December 2008 to December 2009, a similar situation was observed even though, in this trial, the lactobacilli cells were administered once a month. The in vivo results of this study are promising and indicate that a L. johnsonii CRL1647 supplement to beehives favours mainly open and operculated brood areas, demonstrating a stronger stimulation of egg-laying and will become a natural product which will assist the beekeeper both in colony management and the creation of late nuclei and/or bee packages due to its beneficial effects in the beehive colony. © 2011 Wageningen Academic Publishers.